2001
DOI: 10.1002/jca.1000
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of granulocyte and monocyte adsorption apheresis in patients with active ulcerative colitis: A multicenter study

Abstract: Active ulcerative colitis (UC) is characterized by activation and infiltration of granulocytes and monocytes/macrophages into the colonic mucosa. The infiltrated leukocytes can cause mucosal damage by releasing degradative proteases, reactive oxygen derivatives, and proinflammatory cytokines. The aim of this trial (conducted in 14 specialist centers) was to assess safety and efficacy of granulocyte and monocyte adsorption apheresis in patients with active UC most of whom were refractory to conventional drug th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
350
0
6

Year Published

2002
2002
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 257 publications
(371 citation statements)
references
References 26 publications
15
350
0
6
Order By: Relevance
“…Whereas anti-TNF therapy in CD indirectly lowers PMN concentrations in the intestinal mucosa (55), direct Ab-mediated integrin neutralization has resulted in promising efficacy profiles in both CD and ulcerative colitis (56,57). A small clinical trial using a small molecule inhibitor of c-Raf, a critical upstream kinase of p38 MAPK and JNK, showed beneficial effects in CD and included a reduction of activated PMNs in the inflamed mucosa of the responders (58,59).…”
Section: Discussionmentioning
confidence: 99%
“…Whereas anti-TNF therapy in CD indirectly lowers PMN concentrations in the intestinal mucosa (55), direct Ab-mediated integrin neutralization has resulted in promising efficacy profiles in both CD and ulcerative colitis (56,57). A small clinical trial using a small molecule inhibitor of c-Raf, a critical upstream kinase of p38 MAPK and JNK, showed beneficial effects in CD and included a reduction of activated PMNs in the inflamed mucosa of the responders (58,59).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the fact that PMN depletion is associated with maintenance of CTL-dependent antiviral effects but diminished tissue damage may help the design of potential immunotherapeutic approaches for the treatment of HBV infection in chronically infected patients. This should also be viewed in light of the fact that PMN depletion is a relatively simple procedure that has been performed in humans for the treatment of conditions such as inflammatory bowel disease and ulcerative colitis (29).…”
Section: Depletion Of Pmns Blocks the Recruitment Of Antigen-nonspecificmentioning
confidence: 99%
“…13 Therefore, reducing granulocytes and monocytes by apheresis has the potential for improving the bowel inflammation and patient status. Recently, granulocyte and monocyte adsorptive apheresis (GMCAP) has been tried as a novel approach for autoimmune diseases such as rheumatoid arthritis 14,15 and UC [16][17][18][19][20][21][22] which poorly respond to medication. Several studies have assessed safety and efficacy of GMCAP for patients with active UC.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have assessed safety and efficacy of GMCAP for patients with active UC. Shimoyama et al 18 reported that 58.5% of 53 patients, most of whom were refractory to conventional drug therapy had remission or improved after five apheresis sessions and the daily dose of prednisolone was reduced. Only eight non-severe adverse effects were noted in five patients.…”
Section: Introductionmentioning
confidence: 99%